الفرص والتحديات التى تواجهها جامعة تبوك فى ظل مشروع نيوم: دراسة ميدانية من وجهة نظر الطلاب وأعضاء هيئة التدريس بالجامعة - الحسين، خلف محمد خلف (جامعة أسيوط - مركز تطوير التعليم الجامعي, 2019)
Through its vision of 2030, Saudi Arabia seeks to become a leading global model in various aspects of life. The vision was comprehensive and established the future of the Kingdom through a series of investment and development projects giant aimed at transforming the Kingdom's economy and diversifying the country's sources of income away from dependence on oil. The new project is one of the most important of these projects and will attract private investments, investments and government partnerships by focusing on nine specialized investment sectors: the future of energy and water, the future of mobility, the future of biotechnologies, the future of food, the future of technical and digital sciences, the future of advanced manufacturing and the future of media and media production. The strategic location of Tabuk University is an important catalyst to play a leading role in contributing to making the NEOM project a reality. In this context, this research proposal will identify the role of the University of Tabuk in contributing to the NEOM project as well as the possibility of development in some areas of the university while achieving the largest participation and usefulness in the project. The study sample will consist of 200 faculty members and 1000 students who will be selected randomly from all stages to try to represent the study community as much as possible.
تسعى المملكة العربية السعودية من خلال رؤيتها الطموحة 2030 لأن تصبح نموذجاً عالمياً رائداً في مختلف جوانب الحياة. الرؤية جاءت شاملة وتؤسس لمستقبل المملكة من خلال جملة من المشاريع الاستثمارية والتنموية العملاقة التي تهدف إلى تحويل اقتصاد المملكة وتنويع مصادر البلاد من الدخل بعيداً عن اعتمادها على النفط. ويشكل مشروع نيوم إحدى أهم هذه المشاريع وسيعمل على استقطاب الاستثمارات الخاصة والاستثمارات والشراكات الحكومية من خلال التركيز على 9 قطاعات استثمارية متخصصة وهي: مستقبل الطاقة والمياه ومستقبل التنقل ومستقبل التقنيات الحيوية ومستقبل الغذاء ومستقبل العلوم التقنية والرقمية ومستقبل التصنيع المتطور ومستقبل الإعلام والإنتاج الإعلامي ومستقبل الترفيه ومستقبل المعيشة الذي يمثل الركيزة الأساسية لباقي القطاعات. تم وضع استبانة محكمة لمعرفة ما هي الفرص والتحديات والتي تواجه جامعة تبوك في ضوء مشروع نيوم. وقد بينت استجابات أفراد العينة إلى اتفاق جميع أفراد عينة الدراسة على دور جامعة تبوك في التعريف بمشروع نيوم ورؤية المملكة 2030 ومشروع نيوم. كما بينت الدراسة أن لدى جامعة تبوك فرص كثيرة تمكنها من أن تكون من المؤسسات الرائدة في مشروع نيوم. كما أن الدراسة بينت أن جامعة تبوك تعاني من بعض التحديات التي يجب أن تتجنباها وتعمل على نخطيها للمساهمة بشكل فاعل في مشروع نيوم.
Keywords: السياسة التعليمية -- التعليم الجامعى -- طلاب الجامعات -- أعضاء هيئة التدريس -- مشروع نيوم -- جامعة تبوك